Hubungan Dukungan Keluarga dan Peran Perawat Terhadap Motivasi Pengendalian Tekanan Darah pada Penderita Hipertensi - Rifa’atuk Mahmudah; Rian Tasalim; Ayaturahmi Ayaturahmi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Hypertension is one of the most common cardiovascular diseases. Efforts to control hypertension must start from the individual, so motivation is needed in carrying out the therapy program. Hypertension control also requires support from family, both morally and materially. The role of nurses as care givers, educators and health promoters can provide information to prevent complications. The research purpose to find out the correlation between family support and the role of nurses on the motivation to control blood pressure in hypertensive patients at UPT Rawat Inap Alabio Public Health Center. The research Methods was quantitative with a cross sectional design. The sample is hypertensive patients at UPT Rawat Inap Alabio Public Health Center on December 2021 - January 2022 totaling 306 people, that were taken using a purposive sampling technique. The data was taken questionnaire. The data was analyzed using Chi-Square test. Research result most of the family support was good with the number of 162 people (52.9%), most of the respondents stated that the nurse's role was quite good with the number of 154 people (50.3%) and most of the motivation to control the respondent's blood pressure was good with the number of 206 people (67.3%). There was a correlation between family support (p-value = 0.000 <0.05) and the role of nurses (p-value = 0.039 <0.05) on the motivation to control blood pressure in hypertensive patients at UPT Rawat Inap Alabio Public Health Center. The results of this study show there was a correlation between family support and the role of nurses on the motivation to control blood pressure in hypertensive patients at UPT Rawat Inap Alabio Public Health Center.